DEVELOPMENT OF AUGMENTED REALITY APPLICATION FOR GEOMETRY LEARNING USING THE MARKER BASED TRACKING METHOD - Pratama, Pangeran Fadillah; Hamzah, Muhammad Luthfi; Idria Maita; Megawati, Megawati; Ahsyar, Tengku Khairil (Informatika, Universitas Jenderal Soedirman, 2024)
The role of teachers in implementing innovative and creative learning models in the era of industrial revolution 4.0 is an important influence in attracting student’s attention to achieve learning goals. Student’s lack of interest and motivation to learn is a factor in the difficulty of understanding basic mathematical concepts, especially geometric material. Apart from that, it can be seen from the student’s enthusiasm for learning who easily get bored when studying using books alone. The aim of this research is to develop and apply an Android-based augmented reality (AR) application to increase student’s interest in learning and deliver more interactive material. This application uses a marker based tracking method which was developed using the Unity program. The results of application testing using a black box showed that all application features were used successfully without errors. The pre-test and post-test of 19 grade 6 students regarding understanding of geometry material before and after using AR obtained an increase from 60.53 to 86.84. The system usability scale (SUS) test was aimed at teachers and students by providing 10 statements to assess user satisfaction with the application which received a score of 77.84 in the acceptable category. Evaluation of application usability using 3 matrices, namely learnability, obtained a result of 94%, user efficiency in completing tasks was 0.19 goal /sec, and the error matrix obtained a value of 0.44.